Development of New Shaped Punch to Predict Scale‐up Issue in Tableting Process. Issue 1 (11th November 2013) - Aoki, Shigeru; Uchiyama, Jumpei; Ito, Manabu
<x xml:space="preserve">Abstract</x> Scale‐up issues in the tableting process, such as capping, sticking, or differences in tablet thickness, are often observed at the commercial production scale. A new shaped punch, named the size adjusted for scale‐up (SAS) punch, was created to estimate scale‐up issues seen between laboratory scale and commercial scale tableting processes. The SAS punch's head shape was designed to replicate the total compression time of a laboratory tableting machine to that of a commercial tableting machine. Three different lubricated blends were compressed into tablets using a laboratory tableting machine equipped with SAS punches, and any differences in tablet thickness or capping phenomenon were observed. It was found that the new shaped punch could be used to replicate scale‐up issues observed in the commercial tableting machine. The SAS punch was shown to be a useful tool to estimate scale‐up issues in the tableting process. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:235–240, 2014